RADIKALISME AGAMA DALAM PERSPEKTIF HUKUM ISLAM - Said, Hasani Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2015)
Abstract: Religious Radicalism in the Perspective of Islamic Law. The emergence of ISIS (Islamic State of Iraq and Suriah) movement in some countries, including Indonesia, bring back discussions in the study of religious radicalism. This paper examines the religious radicalism of Islam which is often viewed as religious ideas that could potentially give birth to terrorism. The aspects that were examined here includes religious texts- which are often used as a basis of justification to undertake radical movement-methods in understanding the texts, as well as, the implications for perpetrators of radical movements. This study finds out that the birth of a radical ideology is due to a narrow and incomplete interpretation to the religious texts which later implicates in a false understanding of the doctrine of Islam.Abstrak: Radikalisme Agama dalam Perspektif HukumIslam. Mencuatnya fenomena ISIS di berbagai negara, termasuk Indonesia, memunculkan kembali perbincangan hangat kajian-kajian radikalisme agama. Tulisan ini mengkaji gerakan radikalisme agama (Islam) yang sering diopinikan sebagai paham keagamaan yang berpotensi melahirkan terorisme. Aspek-aspek yang dikaji meliputi teks-teks keagamaan yang sering dijadikan pembenaran dalam melakukan gerakan radikal, metode pemahaman terhadap teks-teks agama tersebut, serta implikasinya terhadap pelaku gerakan radikal. Berdasarkan hasil kajian yang penulis lakukan dapat disimpulkan bahwa lahirnya paham radikal adalah disebabkan penafsiran yang sempit dan tidak utuh terhadap nas-nas syara’ yang kemudian berimplikasi pada pemahaman yang keliru terhadap doktrin agama Islam.